Luminescence enhancement of alloyed quantum dots bound to gold nanoparticles by mercaptocarboxylic acids in colloidal complexes. (3rd September 2019) - Kormilina, Tatiana K; Arefina, Irina A; Stepanidenko, Evgeniia A; Kurshanov, Danil A; Cherevkov, Sergei A; Dubavik, Aliaksei; Litvin, Aleksandr P; Baranov, Alexander V; Ushakova, Elena V; Fedorov, Anatoly V
Abstract: The understanding of the physical mechanisms of the nanoobjects interaction within the nanostructured complex materials is one of the main tasks for the development of novel materials with tunable properties. In this work, we develop a formation procedure of the colloidal complexes based on alloyed CdZnSe/ZnS quantum dots and gold nanoparticles where the various mercaptocarboxylic acids are used as the binding molecules. The QD photoluminescence enhancement (up to ×3.1) can be achieved by the control of the interparticle distance in colloidal solutions. We provide a detailed discussion on the influence of the linking molecules on the nanoparticle complexes optical parameters through the steady-state and time-resolved spectral measurements.